1995
DOI: 10.1002/jnr.490400610
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of specific nerve cells in lesioned visual cortex of the human brain: An indirect evidence after constant stimulation with different spots of light

Abstract: The defective parts of the visual field of two brain-injured patients were stimulated with different spots of light. There is evidence for at least five independent visual functions which can be restored due to constant stimulation of the blind part of the visual field: (1) The constant stimulation of the blind part of the visual field with spots of white light leads to an increase of the visual field for the perception of white light only. (2) The constant stimulation with spots of light of different waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Yet there was a small increase of 4.2% in stimulus detection when patients were later tested with high-resolution perimetry and a reduction of the blind field between 3.7% and 4.2% in conventional perimetry on a Tübinger Automatic Perimeter (TAP-2000). This finding is in agreement with earlier reports (e.g., Hyvärinen, Raninen & Näsänen, 2002;Julkunen et al, 2003;Julkunen et al, in press;Kasten et al, 1999;Kasten & Sabel, 1995;Kasten et al, 1998a;Mueller et al, 2003;Poggel, Kasten, Müller-Oehring, Sabel, & Brandt, 2001;Poggel et al, 2004;Potthoff, 1995;Schmielau, 1989;Schmielau, Wong, & Ling, 1998;Werth & Moehrenschlager, 1999;Werth & Seelos, 2005;Wuest, Kasten, & Sabel, 2004). Interestingly, very similar increases were observed in most of our other investigations, which varied between 2% and 8% (please note that the percentage relates to the size of the visual field, which was investigated with two independent perimetric methods including measurement of both intact and defective visual field areas).…”
Section: Discussionsupporting
confidence: 91%
“…Yet there was a small increase of 4.2% in stimulus detection when patients were later tested with high-resolution perimetry and a reduction of the blind field between 3.7% and 4.2% in conventional perimetry on a Tübinger Automatic Perimeter (TAP-2000). This finding is in agreement with earlier reports (e.g., Hyvärinen, Raninen & Näsänen, 2002;Julkunen et al, 2003;Julkunen et al, in press;Kasten et al, 1999;Kasten & Sabel, 1995;Kasten et al, 1998a;Mueller et al, 2003;Poggel, Kasten, Müller-Oehring, Sabel, & Brandt, 2001;Poggel et al, 2004;Potthoff, 1995;Schmielau, 1989;Schmielau, Wong, & Ling, 1998;Werth & Moehrenschlager, 1999;Werth & Seelos, 2005;Wuest, Kasten, & Sabel, 2004). Interestingly, very similar increases were observed in most of our other investigations, which varied between 2% and 8% (please note that the percentage relates to the size of the visual field, which was investigated with two independent perimetric methods including measurement of both intact and defective visual field areas).…”
Section: Discussionsupporting
confidence: 91%
“…Training of incremental thresholds (Zihl, 1980) does appear to produce improvements in other visual functions, e.g., the ability to discriminate colors, as well as visual acuity, while other researchers have reported that each visual function, such as light detection, recognition of shapes, and perception of colors, must be trained separately and that no transfer occurs (Potthoff, 1995;Schmielau, 1989).…”
Section: Discussionmentioning
confidence: 95%
“…Computer technology has increased the scope and duration of cognitive rehabilitation [83], and visual stimulation has been implicated in the restoration of function in brain injured patients. PotthoOE [84] demonstrated that regeneration of speci® c nerve cells in the visual cortex can be promoted with the aid of visual training. The use of VR would provide a means by which such regeneration could be promoted, although precise psychophysiological correlates have yet to be determined [85].…”
Section: Enriching the Therapeutic Environmentmentioning
confidence: 99%